A Comparative Study of Cell Specific Effects of Systemic and Volatile Anesthetics on Identified Motor Neurons and Interneurons of Lymnaea stagnalis (L.), Both in the Isolated Brain and in Single Cell Culture - Fathi Moghadam, Hadi; Yar, Talay; Qazzaz, Munir M.; Ahmed, Ibrahim Abdelrazig; Winlow, William (Frontiers in Physiology, 2019)
1. A comparative study of volatile and systemic general anesthetics revealed important differences in the neuronal responses of identified cell types in the isolated central nervous system (CNS) and cultured identified neurons in single cell culture of Lymnaea stagnalis (L.). 2. At high enough concentrations all anaesthetics eventually caused cessation of spontaneous or evoked action potentials, but volatile anesthetics were much faster acting. Halothane at low concentrations caused excitation, thought to be equivalent to the early excitatory phase of anesthesia. Strong synaptic inputs were not always abolished by pentobarbital. 3. There were cell specific concentration-dependent responses to halothane and pentobarbital in terms of membrane potential, action potential characteristics, the after-hyperpolarisation and patterned activity. Individual neurons generated specific responses to the applied anesthetics. 4. The inhalation anesthetics, enflurane and isoflurane, showed little concentration dependence of effect, in contrast to results obtained with halothane. Enflurane was faster acting than halothane and isoflurane was particularly different, producing quiescence in all cells types studied at all concentrations studied. 5. Halothane, enflurane, the barbiturate general anesthetics, pentobarbital and sodium thiopentone and the dissociative anesthetic ketamine, produced two distinctly different effects which could be correlated with cell type and their location in the brain: either a decline in spontaneous and evoked activity prior to quiescence or paroxysmal depolarising shifts (PDS) again prior to quiescence, which were reversed when the anesthetic was eliminated from the bath. In the strongly electrically coupled neurons, VD1 and RPD2, both types of response were observed. 6) The effects of halothane on isolated cultured neurons indicates that PDS can be generated by single identified neurons in the absence of synaptic inputs. Further, many instances of PDS in neurons that do not generate it in situ have been found in cultured neurons. The nature of PDS is discussed.